2022
DOI: 10.1101/2022.12.08.519585
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indirect genetic effects improve female extra-pair heritability estimates

Abstract: The question of why females engage in extra-pair behaviours is long-standing in evolutionary biology. One suggestion is that these behaviors are maintained through pleiotropic effects on male extra-pair behaviors and lifetime reproductive success (genes controlling extra-pair behaviours are shared between sexes, but only beneficial to one, in this case, males). However, for this to occur extra-pair behaviour must be heritable and positively genetically correlated between sexes. Although previous studies have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…(Reid et al 2011;Grinkov et al 2020). However, Dobson et al. (2023) found that the inclusion of social partner indirect genetic effects (those derived from the behaviour of another) improved model fit for the heritability of both male and female extra-pair behaviour, implying a role for the wider social environment in the plasticity of extra-pair behaviour.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…(Reid et al 2011;Grinkov et al 2020). However, Dobson et al. (2023) found that the inclusion of social partner indirect genetic effects (those derived from the behaviour of another) improved model fit for the heritability of both male and female extra-pair behaviour, implying a role for the wider social environment in the plasticity of extra-pair behaviour.…”
Section: Discussionmentioning
confidence: 94%
“…Although we consider our data to be near-complete, our phenotypic study is still subject to some bias (Hadfield 2008). For example, we sampled chicks for paternity at day two, (see Dunning et al 2023), but this may still exclude an invisible fraction of those pairs, females (Kidd et al 2015) or eggs (Yuta et al 2018;Assersohn et al 2021) who fail early. As a result, our study measures extra-pair paternity, and not extra-pair copulations, which could be more frequent than is reflected in paternity analysis (Fossøy, Johnsen, and Lifjeld 2006;Girndt 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations